Thematic ethno-based learning math skills in ethnomathematics-based learning - Zikir, Al; Walid, Walid; Susilo, Bambang Eko; Kharisudin, Iqbal; Zaenuri, Zaenuri; Sugiman, Sugiman (Universitas Wiralodra, 2024)
This research aims to determine and describe mathematical abilities in ethnomathematics-based learning. The method used in the research is a systematic literature review. The results of article selection from 53 articles published from 2019-2023 based on the ERIC and Scopus databases found 5 articles that met the research objectives. The results of the identification and analysis of articles found that ethnomathematics-based learning can improve mathematical understanding abilities, problem-solving abilities, creative thinking abilities, higher-order thinking abilities, and mathematical connection abilities. Ethnomathematics-based learning can improve students' mathematical abilities. However, existing research has yet to reveal the full range of students' mathematical abilities in learning mathematics. This can be used as a reference for further research.